2020
DOI: 10.1111/ijfs.14914
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship and molecular docking analysis of cysteine‐containing dipeptides as antioxidant and ACE inhibitory

Abstract: QSAR reveals the relationship between the structure of cysteine‐containing dipeptide with antioxidant and ACE inhibitory activity. As a strong multifunctional peptide, CW could be utilized in functional foods owing to less interference in normal life activities, high oral bioavailability and thermostability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The detailed experimental L ( L Exp ) and predicted L ( L Pred ) values with residuals of the stilbene derivatives from the optimal model are listed in Table S2, and the plots between L Exp and L Pred values of the training and test sets are depicted in Figure , which shows good agreement between L Pred and L Exp values, not exceeding 0.2 log unit. Altogether, these data ( q 2 > 0.5, r pred 2 > 0.5) indicated that a reliable HQSAR model with acceptable prediction power was constructed …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The detailed experimental L ( L Exp ) and predicted L ( L Pred ) values with residuals of the stilbene derivatives from the optimal model are listed in Table S2, and the plots between L Exp and L Pred values of the training and test sets are depicted in Figure , which shows good agreement between L Pred and L Exp values, not exceeding 0.2 log unit. Altogether, these data ( q 2 > 0.5, r pred 2 > 0.5) indicated that a reliable HQSAR model with acceptable prediction power was constructed …”
Section: Resultsmentioning
confidence: 77%
“…Altogether, these data (q 2 > 0.5, r pred 2 > 0.5) indicated that a reliable HQSAR model with acceptable prediction power was constructed. 33 Apart from predicting the biological activities of untested compounds, HQSAR analysis also enables the identification of molecular fragments that are associated with the bioactivity by the interpretation of contribution maps presenting atomic contributions to the activity with color coding, where green, green-blue, and yellow denote positive contribution; red, redorange, and orange signify negative contribution, while white reflects intermediate contribution. The contribution maps of the most (5r) and least (5t) active molecules are shown in Figure 5, in which the common backbone was colored cyan.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, dipeptide agents, the shortest peptides, are not only easy to prepare and devoid of toxic metabolites, but they are capable of penetrating biological barriers and are more stable when compared to oligopeptides [27]. Dipeptide derivatives, natural and synthetic, have been investigated for applications in diverse aspects [28][29][30][31]. For example, the cyclic Leuleu dipeptide was isolated and purified from the ethyl acetate extract of a broth of the genus Gordonia sp.…”
Section: Introductionmentioning
confidence: 99%